Dark places - Flynn, Gillian 1971- (Concorde, 2016)
Libby Day was only seven years old when her mother and two sisters were murdered and her brother Ben was jailed for the crime. Now, twenty-five years later, Libby discovers shocking evidence that Ben may be innocent, and the real killer still at large
Original: Großbritannien, Frankreich, USA 2015
Special features: Interviews, Trailer
Keywords: Murder / Investigation / Drama; Brothers and sisters / Drama; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Brothers and sisters; Murder / Investigation; DVD-Video